The Effect of Brand Image and Service Quality on Consumer Decision at Lapstore Bandar Lampung - Bambang Irawan; Osly Usman (Journal of Digital Business and Global Economy, 2026)
This paper investigates the influence of brand image and service quality on the purchase intentions of consumers purchasing laptops from Lapstore. The need for analysis in this research lies in the fact that business in laptops is increasingly competitive in this industry where businesses are challenged to create a good brand and great service in an effort to influence the consumer decision making process. Data collection was conducted by conducting a questionnaire-based collection with Lapstore customers who have previously purchased laptops. For our second analysis, multiple linear regression methods were utilized. The results indicate that brand image and quality of service affect positively and significantly spending decisions on laptops in Lapstore either independently or together. This study highlights the necessity of Lapstore to consider brand image and service quality as the critical indicators to determine consumer purchasing intentions.